Descrição de novas espécies neotropicais de Hirtodrosophila e Mycodrosophila (Diptera, Drosophilidae) baseada em dados morfológicos e moleculares - Santos, João Pedro Junges dos (2013)
The Drosophilidae family is composed by flies displaying different alimentary habits. The most studied species a re associated with yeasts that develop during decomposition of plant substrates such as cacti, flowers and fruits. However, some species with more restrict habits as the predatory species in the subfamily Steganinae or the mycophagous species in different evolutionary lineages in the family, are poorly known. In genera as Hirtodrosophila and Mycodrosophila the information about ecological aspects is scarce and sporadic , particularly in the Neotropics, this scarcity leaves some appearance of several uncertai nties about the systematics and taxonomy from the species of these genera Clarifying some of these issues may be essential to provide a progress in face of the biodiversity crisis that seems to establish and the description of new species is a necessary step in this way. Therefore the aim of this dissertation is to help in the resolution of taxonomic questions related to the Neotropical Hirtodrosophila and Mycodrosophila species (Drosophilidae). Six new species are described, four belonging to Hirtodrosophila and two to Mycodrosophila genera. Those belonging to Hirtodrosophila are included into the H. hirticornis group, three cryptic species occurring together in the Amazon biome and a fourth species similar to H. morgani and common in the Pampa and in the transition between the Pampa and Atlantic Forest biomes. The new Mycodrosophila species have similarities with M. neoprojectans and M. projectans and are distributed in Amazon biome and in the Pampa biome and in the transition between the Pampa and Atlantic Forest biomes respectively. For the descriptions we used an integrative approach between the classical taxonomic school and molecular and morphometric analysis, which revealed especially promising in the search for support to the discovery of new species and its concomitant description.